Proceedings of the 2nd International Conference on Intelligent Manufacturing and Materials 2018
DOI: 10.5220/0007533404450453
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Implementation Effectiveness of the CDIO Education Model

Abstract: The CDIO education model is the latest achievement in the reform of international engineering education in recent years. China introduced the model and initiated pilot implementation in late 2005. After more than ten years of investigation and practical experience, the higher education institutions that participated have developed and consolidated their own training characteristics. Through the analysis of the evaluation standards for engineering personnel as well as elements of the CDIO curriculum, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The spread of CDIO across more than 116 countries is a testament to its adaptability and global appeal (http://www.cdio.org/participate). Various studies have shown the effectiveness of CDIO in enhancing student engagement and outcomes in engineering education (Wang & Yuan, 2018). The approach has been praised for fostering creativity, critical thinking and the ability to tackle complex problems (Yue, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The spread of CDIO across more than 116 countries is a testament to its adaptability and global appeal (http://www.cdio.org/participate). Various studies have shown the effectiveness of CDIO in enhancing student engagement and outcomes in engineering education (Wang & Yuan, 2018). The approach has been praised for fostering creativity, critical thinking and the ability to tackle complex problems (Yue, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%